Yield of elective coronary angiography; gender differences, patient history, risk factors and angiographic findings in a primary care population - Pieta Sundqvist; Essi Pikkarainen; Päivi Rautava; Susa Majaluoma; Päivi E. Korhonen (TAYLOR & FRANCIS LTD, 2025)
ObjectiveTo assess yield of elective coronary angiography and gender differences in primary care patients suspected to have stable coronary artery disease (SCAD).DesignInformation was gathered from an angiography registry, referral texts of the general practitioners and medical records made by the cardiologists in secondary care.SettingAngiography registry data analyses of the Turku University Hospital, Finland, in the year 2011.SubjectsTwo hundred forty-six patients who were referred from primary care to secondary care and underwent coronary angiography for suspected SCAD symptoms.Main outcome measuresGender differences and diagnostic yield of coronary angiography for obstructive CAD.ResultsObstructive CAD was identified in 73%, more often in males than in females (51% vs. 84%, p < 0.001). Thirteen per cent of the patients were over 80 years of age, and 94% of them had obstructive CAD. The prevalence of hypertension was 60%, treatment goal was achieved by 25%.ConclusionThe diagnostic yield of elective coronary angiography was low in women compared to men although there were no substantial differences in evidence-based medication, risk factors or anticipated angina symptoms between genders.